Chronic Mastitis in Egypt and Morocco: Differentiating between Idiopathic Granulomatous Mastitis and IgG4‐Related Disease. Issue 5 (8th June 2016) - Allen, Steven G.; Soliman, Amr S.; Toy, Kathleen; Omar, Omar S.; Youssef, Tamer; Karkouri, Mehdi; Ayad, Essam; Abdel‐Aziz, Azza; Hablas, Ahmed; Tahri, Ali; Oltean, Hanna N.; Kleer, Celina G.; et al.
Abstract: Idiopathic granulomatous mastitis (IGM) is a benign, frequently severe chronic inflammatory lesion of the breast. Its etiology remains unknown and reported cases vary in their presentation and histologic findings with an optimal treatment algorithm yet to be described owing mainly to the disease's heterogeneity. IgG4‐related disease (IgG4‐RD) is a newly recognized systemic fibroinflammatory condition characterized by a dense lymphoplasmacytic infiltrate with many IgG4‐positive plasma cells, storiform fibrosis, and obliterative phlebitis. Immunosuppressive therapy is considered to be an effective first‐line therapy for IgG4‐RD. We sought to clarify and classify chronic mastitis according to the histologic findings of IgG4‐RD mastitis with respect to IGM and to develop a robust diagnostic framework to help select patients for optimal treatment strategies. Using the largest collection to date (43 cases from Egypt and Morocco), we show that despite sharing many features, IGM and IgG4‐RD mastitis are separate diseases. To diagnostically separate the diseases, we created a classification schema—termed the Michigan Classification—based upon our large series of cases, the consensus statement on IgG4‐RD, and the histologic description of IGM in the literature. Using our classification, we discerned 17 cases of IgG4‐RD and 8 cases of IGM among the 43 chronic mastitis cases, with 18 indeterminate cases. Thus, our Michigan Classification can form the basis of rational stratification of chronic mastitis patients between these two clinically and histopathologically heterogeneous diseases.